The Morphological, Anatomical and Physiological Responses of Kemiri Sunan (Reutealis trisperma) Under Drought Stress - Nisa, Amanatun; Devita , Harijayanti; Riki , Kurniawan (BIOVALENTIA: Biological Research Journal, 2025)
Reutealis trisperma is a promising bioenergy crop, exhibits notable drought stress responses that influence its morphology, physiology, and anatomy. However, the information about Reutealis trisperma under drought stress was still limited. Therefore, we conducted this study to evaluates the plant's adaptive mechanisms under controlled greenhouse conditions with varying levels of drought stress of Reutealis trisperma. We used a completely randomized design (CRD) with drought stress as the treatment and 10 repetitions. Drought stress was applied by withholding water, with treatments divided into mild stress (2 weeks) and suffer stress (7 weeks). Control plants were watered regularly. We measured some morphological parameters (plant height, number of leaves, dry weight), physiological parameters (RWC, MDA, proline, chlorophyll content), and anatomical parameters (stomatal density and structure). Data were analysed using ANOVA with a 0.05 significance level. Results revealed a decline in plant height, chlorophyll content, and relative water content (RWC), alongside an increase in malondialdehyde (MDA) levels, indicating oxidative stress. Morphological changes included reduced leaf and root biomass, while anatomical adaptations featured reduced stomatal density to conserve water. Reutealis trisperma exhibits significant morphological, physiological, and anatomical adaptations under drought stress. Drought reduced plant height, chlorophyll content, and relative water content while increasing root-to-leaf dry weight ratios and malondialdehyde levels, indicating oxidative stress. Anatomical changes, such as reduced stomatal density, enhance water conservation. These adaptations underscore the plant's resilience, supporting its potential for bioenergy production on marginal, water-deficient lands.